(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
This study examines structural transformation and sectoral linkages in Indonesia by analyzing 34 provinces through the 2016 Interregional Input–Output (IRIO) table updated to 2023 using the RAS method. Provinces are categorized into agriculture-based, transforming type A and B, and urban regions by combining agricultural sector contribution and rural poverty levels. The results show that Indonesia remains predominantly in a transforming stage, with only modest shifts over the past decade despite substantial changes in provincial economic structures. Analysis of 1,649 sector–region input units reveals that 10.1 percent hold leading status, although none are from the agricultural sector, indicating shallow upstream and downstream linkages in agriculture. Agricultural-based regions exhibit the lowest productivity and weakest sectoral depth, yet demonstrate the highest marginal GDP multipliers when stimulated, suggesting significant untapped growth potential. A Rp1 trillion increase in final demand generates an average GDP impact of Rp932.5 billion and approximately 128,300 potential jobs, with the strongest labor effects occurring in transforming regions. Interprovincial spillovers remain limited, dominated by intra-regional effects, highlighting fragmented regional integration. Overall, the findings demonstrate that accelerating Indonesia’s transformation requires strengthening manufacturing and service linkages around agricultural regions while deepening cross-provincial value chains to reduce persistent spatial inequality.